AGUASCALIENTES TEXTILE MICRO-ENTERPRISES: PIONEERING E-MARKETING AND INNOVATIONMARÍA ALEJANDRO - Fernández , González; Pérez, Sofia Rodriguez (International Journal of Allied Research in Marketing and Management (IJARMM), 2023)
This study addresses the pressing issue of sustaining micro, small, and medium-sized enterprises (MSMEs) in the competitive market landscape. In today's business environment, enhancing competitiveness and performance is imperative for their survival. Despite the global significance of this challenge, a significant proportion of these businesses face early closure, reflecting a shared trend both in Mexico and worldwide. The textile industry in Aguascalientes, Mexico exemplifies this vulnerability, marked by traditional practices and stagnant growth. This research focuses on micro-companies within this sector, which are particularly susceptible. The global textile industry's substantial valuation and consistent growth underscore its economic importance. Mexico stands as a vital player alongside China, India, and Bangladesh. Despite employing a substantial workforce, this sector is grappling with neglect, leaving numerous businesses on the brink of collapse. This study intends to address this neglected sector's challenges and devise strategies for the revitalization of micro-textile businesses in Aguascalientes. By exploring innovative approaches and modernizing traditional practices, this research aims to contribute to the sector's resurgence, thereby benefiting both the local economy and the broader textile industry. Through a comprehensive analysis, this study seeks to equip MSMEs with tools to not only navigate the competitive landscape but also thrive and evolve